Analisis Strategi Pengelolaan Pembiayaan dalam Anggaran Dana Pendidikan di SMK Negeri 1 Tekarang - Ilham; Nuraini Asriati (Journal of Mandalika Literature, 2024)
The purpose of this study is to analyze the strategies used by SMK Negeri 1 Tekarang in planning, implementing (in this case using), and evaluating financing from two sources of education funds, namely BOS and PBP. This study uses a qualitative approach with a descriptive method obtained from a case study. Data collection through observation, interviews, and analyzing documents related to financing management at SMK Negeri 1 Tekarang. The findings show that financing management at SMK Negeri I Tekarang has been implemented in accordance with the principles of accountability and transparency. However, there are still several challenges such as limited financial resources and the many items that need to be met so that the budget seems small. This study provides recommendations to improve the effectiveness of cash management, including strengthening staff capacity and increasing collaboration with external stakeholders. The importance of this study is expected to help improve the quality of educational resource management in these schools and help them achieve better educational goals.